Epidemiology, resistance characteristics, virulence determinants, and treatment outcomes of Staphylococcus aureus bone and joint infections: a one-year prospective study at a tertiary care hospital in India. (16th November 2020) - Banerjee, Barnini; Shaw, Tushar; Mukhopadhyay, Chiranjay; Bhat N, Shyamasunder; Singh, Brij Mohan Kumar
ABSTRACT: Purpose: The study was aimed to explore the differences between the Staphylococcus aureus osteosynthesis-associated infection (OAI) and non-implant related infections (NIRI) in terms of epidemiology, resistance characteristics, virulence determinants, treatment, risk factors, and outcome. Methods: A prospective study was conducted from 2018 through 2019. The phenotypic and genotypic characterization of S. aureus, risk factors, treatment, and outcome were compared. Results: A total of 60 patients were included. 50% had OAIs (70%) (p = .045). Overall, MRSA (OR 0.69; p = .020) and old age (OR 0.95; p = 0.035) were the important risk factors. Implanted patients presented with the features of chronic osteomyelitis (93.3%, p = 0.01). NIRI cases composed of only 66.7% of OM, and 55% of them were acute. OAI isolates were more frequently luk gene positives (50%) than isolates from the NIRI group (33.3%). Patients with OAI by luk positive isolates significantly had prolonged hospital stay (p = 0.043; OR-0.96, CI-0.91–1.0) . Most of the NIRIs (60%) managed with antibiotics, but frequent surgical intervention (OR 10.68; p = .024) with prolonged systemic antibiotics (OR 1.07; p = .029) helped all OAIs to recover. Patients without implants were recovered in a higher number (83.3%). Conclusion: Our study highlighted that the differences exist between the OAI and NIRI, specifically in terms of clinical features, distribution of luk genes, treatment approach, and outcome. Risk factors for both types of infection remained the same.